(untitled) (Palíndromo, 2017)
The aim of this text is to study the poetics achieved in the pictorial narrative of Iuli Klever (1850-1924) due to his use of the elements and resources of Romanticism. We try to understand, through the creative profile of this artist, whether such works bring with them a greater overlap of romanticism in the face of lyricism, or if lyricism overlaps with Romanticism, the former being a characteristic of the latter. To do so, we first performed a description of the Romantic worldview, which was motivated by another aesthetic, appreciated to expose the human being involved in his own feelings and thoughts, and presented a remarkable appreciation for the landscape associated with the poetics required for expressive originality. In a second moment, we find that although the artist uses all the elements of Romanticism in his pictorial narratives, like the mythical, because of the enchantment of the form and the colors of the works occurs the prevalence of lyricism in front of the other characteristics of Romanticism. We also verify that in all his works the sky stands out as the essential character, from where all the distribution of colors and forms is projected to the landscape and the other characters.